Effect of bypass protein on yield and composition of milk in crossbred cows* - Kalbande, V H; Thomas, C T (The Indian Journal of Animal Sciences, 2012)
Jersey crossbred cows (18) were divided into 3 graups (1, 2 and 3) of 6 animals each as unifarmly as possible with regard to their body weights and milk production and maintained on 3 respective isonitrogenous and isocaloric concentrate mixtures A, Band C with varying rumen degradable pratein (RDP) to undegradable dietary protein (UDP) ratios of 37:63; 52:48 and 70:30 for 100 days starting fifth day pastpartum. The feed intake of animals was increased significantly (P